2020
DOI: 10.1002/rra.3643
|View full text |Cite
|
Sign up to set email alerts
|

River embankments mitigate the loss of grassland biodiversity in agricultural landscapes

Abstract: Agricultural intensification has resulted in severe declines in the extent and diversity of seminatural habitats in Europe, whereas the extent of secondary habitats has increased considerably. River embankments have become one of the most extensive and widespread secondary habitats in former floodplains. We compared the diversity patterns of secondary dry and wet grasslands on river embankments with those of seminatural dry and wet grasslands in a Hungarian agricultural landscape using the following community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
3
14
0
1
Order By: Relevance
“…Due to the dense seed bank, high dispersal ability and high regeneration potential of weeds and generalists, they have a higher chance to re-establish in the disturbed patches than specialists; thus, in the long term, their populations dominate these habitats (Cousins 2006). Even though linear landscape elements have the potential to act as green corridors for grassland specialists given their connections to continuous grasslands (Bátori et al 2016(Bátori et al , 2020, they may also provide corridors for generalist and weed species, especially in transformed landscapes (Fekete et al 2018), where their spread is enhanced by transportation and by mowing machinery (Tikka et al 2000).…”
Section: Shannon Diversity and Species Richnessmentioning
confidence: 99%
“…Due to the dense seed bank, high dispersal ability and high regeneration potential of weeds and generalists, they have a higher chance to re-establish in the disturbed patches than specialists; thus, in the long term, their populations dominate these habitats (Cousins 2006). Even though linear landscape elements have the potential to act as green corridors for grassland specialists given their connections to continuous grasslands (Bátori et al 2016(Bátori et al , 2020, they may also provide corridors for generalist and weed species, especially in transformed landscapes (Fekete et al 2018), where their spread is enhanced by transportation and by mowing machinery (Tikka et al 2000).…”
Section: Shannon Diversity and Species Richnessmentioning
confidence: 99%
“…We found that crane‐disturbed areas provided floral resources for a longer time and in larger quantity than undisturbed grassland (Table 2, Figure 4). This can support the maintenance of insect diversity, especially pollinator assemblages and palynivores (Bátori et al, 2020). This service has an especially high conservation importance in grass‐dominated habitats such as the studied ecosystem with relatively few nectar‐producing plants.…”
Section: Discussionmentioning
confidence: 99%
“…Communities that combine subsets of the native species pool and disturbance‐tolerant, functionally distinct groups of species also show this pattern compared to intact communities (Bátori et al. 2020 ). This indicates that high functionality is not necessarily a good indicator of restoration success or intactness, even though recommended by some studies (Laughlin 2014 ).…”
Section: Discussionmentioning
confidence: 99%